2008
DOI: 10.1007/s10653-008-9226-1
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of iron and arsenic in the Chandina alluvium of the lower delta plain, Southeastern Bangladesh

Abstract: Accumulations of iron, manganese, and arsenic occur in the Chandina alluvium of southeastern Bangladesh within 2.5 m of the ground surface. These distinctive orange-brown horizons are subhorizontal and consistently occur within 1 m of the contact of the aerated (yellow-brown) and water-saturated (gray) sediment. Ferric oxyhydroxide precipitates that define the horizons form by oxidation of reduced iron in pore waters near the top of the saturated zone when exposed to air in the unsaturated sediment. Hydrous Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Adsorption and co-precipitation are the main processes controlling As mobility; this element can be sorbed onto different mineral surfaces: clay, oxyhydroxides of Fe, Mn, Al and calcite (Romero et al 2004), and it can be associated with organic matter (Fu et al 2013). Higher correlation of As with TOC than with TIC in Netiesos, Šlavė and Kudrė-915 sections corresponds to the statement of Reimann et al (2003) that organic matter may have a marked influence on As concentration and to the findings of Meharg et al (2006) andzahid et al (2009). Besides, our investigation has shown that accumulation of OM and carbonates in interglacial sediments often occurs simultaneously.…”
Section: Discussionmentioning
confidence: 69%
“…Adsorption and co-precipitation are the main processes controlling As mobility; this element can be sorbed onto different mineral surfaces: clay, oxyhydroxides of Fe, Mn, Al and calcite (Romero et al 2004), and it can be associated with organic matter (Fu et al 2013). Higher correlation of As with TOC than with TIC in Netiesos, Šlavė and Kudrė-915 sections corresponds to the statement of Reimann et al (2003) that organic matter may have a marked influence on As concentration and to the findings of Meharg et al (2006) andzahid et al (2009). Besides, our investigation has shown that accumulation of OM and carbonates in interglacial sediments often occurs simultaneously.…”
Section: Discussionmentioning
confidence: 69%
“…Iron (Fe): Chemical weathering and erosion of mountain belts influence the distribution of trace metal influx to the ocean, sediments carried by the rivers and groundwater flow (Dowling et al 2003;Zahid et al 2008). The concentrations of iron vary from 24,367.4 to 27891 mg/kg with the mean concentrations of 26,310.77 mg/kg.…”
Section: Sulphur (S)mentioning
confidence: 99%
“…Chlorite, kaolinite and feldspar comprise 9.80% of the sediments. Illite is identified by peak 10 Å (001) and distinguished from mica by the narrowing nature of the diffractograms (Zahid et al 2008). Chlorite is identified by the 14 Å peak, and kaolinite is recognized at 7 Å. Lavendulan [Na, Ca, Cu 5 (AsO 4 ) 4 Cl.…”
Section: Clay Mineralogy Of the Sedimentsmentioning
confidence: 99%
“…The natural arsenic contamination, as well as in the case of iron and manganese, is affected by a whole range of (bio)geochemical processes that determine the nature and mobility of arsenic under various reductive conditions [8]. The main processes, determining the access of arsenic into the water are associated with reductive dissolution of arsenic-containing minerals (e.g., arsenopyrite), or iron and manganese oxyhydroxides as well as other iron and manganese compounds with adsorbed arsenic [7,8,9]. Such dissolution is possibly related to the spatial and seasonal changes in the reductive status of the infiltration zone due to the fluctuations of groundwater level and changes in the activity of microorganisms [8].…”
Section: Case Study I: Orp and Surface Water Infiltration Into Groundmentioning
confidence: 99%